2015
DOI: 10.1055/s-0035-1547254
|View full text |Cite
|
Sign up to set email alerts
|

The Beneficial Effects of the DPP-4 Inhibitor Alogliptin on Hemoglobin A1c and Serum Lipids in Japanese Patients with Type 2 Diabetes

Abstract: It has been reported that dipeptidyl peptidase-4 (DPP-4) inhibitors improve hemoglobin A1c (HbA1c) levels in diabetic patients and may also improve the serum lipids. However, few studies have examined relationship between the effects of the DPP-4 inhibitor and the pretreatment HbA1c levels in diabetic patients. Furthermore, it has been reported that prolonged treatment with DPP-4 inhibitors may make glycemic control difficult in some patients. In the present study, we investigated (1) the effect of the DPP-4 i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…More than 80% of AEs reported in each group were mild. A total of 26 serious adverse events (SAEs) occurred in 24 patients (7,8 and 9 patients in the S/G2, G1/G2 and G2/G2 groups, respectively).…”
Section: Safety Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…More than 80% of AEs reported in each group were mild. A total of 26 serious adverse events (SAEs) occurred in 24 patients (7,8 and 9 patients in the S/G2, G1/G2 and G2/G2 groups, respectively).…”
Section: Safety Resultsmentioning
confidence: 99%
“…Although this study revealed that the HbA1c-lowering effect of alogliptin was not attenuated after switching from sitagliptin, the number of patients (6) was very small. 8 In another retrospective cohort study, the subjects were 92 patients with T2DM whose prescription for sitagliptin 50 mg qd was switched to vildagliptin 50 mg bid. The per protocol analysis showed that switching to vildagliptin 50 mg bid significantly lowered HbA1c levels.…”
Section: Discussionmentioning
confidence: 99%
“…Although the hypoglycemic effect of sitagliptin is widely recognized, its hypolipidemic effect has not been thoroughly studied. Previous studies have shown that sitagliptin, as an inhibitor of DPP-4 does not directly participate in the metabolism of blood lipids, but it can indirectly reduce blood lipids by acting on sympathetic reflex and enhancing postprandial lipid mobilization and degradation [12]. Some studies have also suggested that sitagliptin increases blood level of GLP-1 which acts on the hypothalamus, and decreases appetite, calorie and fat ingestion by reducing gastric emptying time and increasing satiety [13].…”
Section: Discussionmentioning
confidence: 99%
“…This is in line with other studies that have shown better glycaemic control when adding DPP-4i therapy to metformin, insulin or sulfonylureas. 27 In the present study the level of 1,5-AG was measured as a short term marker for glycemic control since it has been found to be a more sensitive tool to check day to day glycemic control. 28 The 1,5-AG values and postprandial glucose levels showed an overall decrease and this tendency toward improvement suggested the possibility that alogliptin might improve postprandial hyperglycaemia.…”
Section: Glycaemic Control and Hypoglycaemic Episodesmentioning
confidence: 97%